2019
DOI: 10.3390/jcm8081119
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Treatment of Femoral Shaft Fractures: Comparison between Anterograde Intramedullary Nailing and Monoaxial External Fixation

Abstract: Background: Femoral shaft fractures result from high-energy trauma. Despite intramedullary nailing (IMN) representing the gold standard option of treatment, external fixation (EF) can be used temporarily for damage control or definitively. The purpose of this study is to compare two different options, anterograde IMN and monoaxial EF, for the treatment of femoral shaft fractures. Methods: Between January 2005 and December 2014, patients with femoral shaft fractures operated on in two centers were retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The Ilizarov external fixation technique has been used for the last five decades for the management of long-bone infected nonunions. This method uses percutaneously-inserted fine wires which are tensioned to provide a stiff and stable frame construct [1][2][3][4][5][6]. It permits the realization of compression, distraction, bone-lengthening, and deformity correction.…”
Section: Introductionmentioning
confidence: 99%
“…The Ilizarov external fixation technique has been used for the last five decades for the management of long-bone infected nonunions. This method uses percutaneously-inserted fine wires which are tensioned to provide a stiff and stable frame construct [1][2][3][4][5][6]. It permits the realization of compression, distraction, bone-lengthening, and deformity correction.…”
Section: Introductionmentioning
confidence: 99%
“…With a DOTOR, the operative surgeon might also feel less burdened by the constraints of previously scheduled daytime cases and more comfortable performing a slightly longer case (intramedullary nailing) as opposed to stabilizing the patient with an external fixator. 15 This finding contrasts with that observed in a study conducted by Wixted et al 2 who found a delay from 5.7 to 10.9 hours from presentation to definitive fixation after implementation of a DOTOR. This difference could be due to an increased delay that our institution experienced regarding add-on trauma cases before having the DOTOR in comparison with their institution.…”
Section: Discussionmentioning
confidence: 64%
“…With a DOTOR, the operative surgeon might also feel less burdened by the constraints of previously scheduled daytime cases and more comfortable performing a slightly longer case (intramedullary nailing) as opposed to stabilizing the patient with an external fixator. 15…”
Section: Discussionmentioning
confidence: 99%
“…Internal fixation contributes to anatomic reduction, whereas it is the most invasive form and carries a higher risk of infection, prone to result in devastating complications in the presence of severely compromised soft tissues [5][6][7] . Monolateral external fixation characterized by simple, effective, and minimally invasive, which can preserve the biomechanical microenvironment needed for fracture healing, playing an important role over the years in the treatment of open fractures, or to reconstruct missing or short bones, where internal fixation is impossible or inadvisable [ 1 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%